Konflik Tanah Masyarakat Adat Papua Dalam Film Pesta Babi Perspektif Keadilan Jhon Bordley Rawls - Fajar Illahi; Andri Umar Soleh; Zulfan Taufik (Jurnal Dialektika Hukum, 2026)
This study examines the representation of indigenous Papuan land conflicts in the film Pesta Babi through the perspective of John Bordley Rawls’ theory of justice. The research aims to reveal the forms of social injustice, the marginalization of indigenous communities, and the power relations represented in the film. This study employs a qualitative approach using library research and content analysis methods. Primary data were obtained from the film’s scenes, dialogues, visual symbols, and narrative structure, while secondary data were derived from books, academic journals, and scholarly documents related to land conflicts, human rights, and Rawls’ theory of justice. The findings indicate that Pesta Babi portrays land conflict as a humanitarian issue closely associated with the loss of cultural identity, the right to life, and the spiritual space of indigenous Papuan communities. From the perspective of justice as fairness, the study demonstrates that the state has not been able to provide distributive justice, protection of fundamental rights, and equal participation for indigenous peoples. Furthermore, the film functions as a medium of social criticism toward unequal power relations and inhumane development practices affecting indigenous Papuan communities.